2022
DOI: 10.1177/1098612x221079709
|View full text |Cite
|
Sign up to set email alerts
|

Feline neonatology: From birth to commencement of weaning – what to know for successful management

Abstract: Practical relevance: Despite considerable interest in the field of companion animal reproduction, feline neonatology remains largely unstudied. This contrasts with the need for a more professional veterinary approach to newborn kittens and feline husbandry, across the pet, breeding cattery and rescue shelter settings, to reduce kitten mortality. Global importance: Feline neonatology has relevance for veterinarians around the world as cats are continuing to become established as popular companion animals. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…The number of factors that can affect the mother’s condition during this period is countless [ 12 ]. Age, genetics, nutrition, vaccination status, and the presence of infectious diseases, among other maternal conditions, can directly interfere with litter survival [ 13 , 19 , 20 ]. A study has shown that these maternal factors can affect more than 30% of kennels [ 5 ] and can lead to a 9% mortality rate in newborn dogs [ 2 ].…”
Section: Pregnancy and Prenatal Carementioning
confidence: 99%
See 3 more Smart Citations
“…The number of factors that can affect the mother’s condition during this period is countless [ 12 ]. Age, genetics, nutrition, vaccination status, and the presence of infectious diseases, among other maternal conditions, can directly interfere with litter survival [ 13 , 19 , 20 ]. A study has shown that these maternal factors can affect more than 30% of kennels [ 5 ] and can lead to a 9% mortality rate in newborn dogs [ 2 ].…”
Section: Pregnancy and Prenatal Carementioning
confidence: 99%
“…Metabolic disorders such as diabetes mellitus in the bitch have been associated with fetal loss due to persistent hyperglycemia and the development of large puppies with a higher risk of fetal dystocia. Other metabolic abnormalities, such as hypothyroidism, puerperal hypocalcemia, and pregnancy toxemia, can result in fetal or neonatal loss [ 13 , 35 ]. In addition, prenatal and postnatal nutrition contribute to the metabolic programming of the puppies and kittens.…”
Section: Pregnancy and Prenatal Carementioning
confidence: 99%
See 2 more Smart Citations
“…Further details on the veterinary approach in the case of suspected illness are given in an accompanying review on feline neonatology. 185…”
Section: Clinical Approach To Specific Problems In the Catterymentioning
confidence: 99%